Penerapan Kepemimpinan Otentik Dalam Meningkatkan Kualitas Pelayanan Penumpang Pada Po. Haryanto Divisi Madura - Muhammad Rizki Adilla Fatah; Kania Fitri Alyaa Nugraha; Febri Dwi Prakoso; Firnanda Noeria Rizkiana; Mochammad Isa Anshori (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Constantly changing business dynamics and changing customer preferences require company management to adapt. Customers who now have higher levels of wealth not only want efficient transportation, but also value comfort during travel. This means they need a comfortable vehicle, friendly service and a pleasant atmosphere to enjoy their trip. Therefore, companies must provide first-class service and satisfy their customers by highlighting added value compared to their competitors. The aim of the article is to analyze the application of authentic leadership in improving the quality of passenger service at PO. Haryanto Madura Division. The researcher used descriptive observational research methods. The descriptive research method is an Approach that aims to create an objective picture or description of a situation. .